Anti-Bacterial Activity of Novel Synthesized Chalcone Against S. epidermidis and S. aureus Isolated from Packed Red Cell Blood Product - Aulia Rahman; Wiwit Sepvianti; Serafica Btari Christiyani Kusumaningrum; Arum Sari; Mohd Nazil Salleh (International Journal of Advanced Health Science and Technology, 2022)
Bacterial contamination in blood product was still a problem in Indonesia. Various studies to improve the safety of blood product by inhibiting the bacterial growth in blood product was developed. Chalcone, is one of the natural compounds that has ability to inhibit the bacterial growth, so it can be possible to use that compound for anti-bacterial use in the future. This study aim is to evaluate the anti-bacterial activity of novel synthesis chalcone (E)-1-(4-hydroxyphenyl)-3-phenylprop-2-en-1-one against S. epidermidis and S. aureus isolated from packed red cell blood product. A novel chalcone was synthesized by Claisen-Schmidt Methods while anti-bacterial activity test was done by Agar Diffusion Methods. Chalcone that has been synthesized then characterized by Fourier Transform Infra-Red (FTIR) Methods and Gas Chromatography – Mass Spectrometry (GC-MS). Chalcone was synthesized through a condensation reaction between an aldehyde (benzaldehyde) and ketone (acetophenone) with NaOH as alkaline catalyst. The results from sedimentary analysis using FTIR showed an absorption of the C=C group in the typical medium of chalcone compounds, at the wave number of 1516.96 cm-1. The results of GC-MS characterization resulted a GC chromatogram with one peak with time of retention (tR) 19.68 minutes and relative purity 100%. MS mass spectrum shows that the molecular ion (M+) of this compound was detected at 224 which equivalents to the molecular weight of the chalcone compound. Anti-bacterial test showed that the synthetic chalcone compound with 5% concentration had an inhibitory ability of 56.02% on S. epidermidis and 54.10% on S. aureus, while 2.5% chalcone concentration had an inhibitory ability of 29.17% on S. epidermidis and 50.45% on S. aureus, and 1.25% chalcone concentration had inhibitory ability 0% on S. epidermidis and 37.27% on S. aureus.